Affinity Purification of Protein Complexes in C. elegans - Zanin, Esther; Dumont, Julien; Gassmann, Reto; Cheeseman, Iain; Maddox, Paul; Bahmanyar, Shirin; Carvalho, Ana; Niessen, Sherry; Yates, John R.; Oegema, Karen; Desai, Arshad (Methods in Cell Biology, 2011)
C. elegans is a powerful metazoan model system to address fundamental questions in cell and developmental biology. Research in C. elegans has traditionally focused on genetic, physiological, and cell biological approaches. However, C. elegans is also a facile system for biochemistry: worms are easy to grow in large quantities, the functionality of tagged fusion proteins can be assessed using mutants or RNAi, and the relevance of putative interaction partners can be rapidly tested in vivo. Combining biochemistry with function-based genetic and RNA interference screens can rapidly accelerate the delineation of protein networks and pathways in diverse contexts. In this chapter, we focus on two strategies to identify protein-protein interactions: single-step immunoprecipitation and tandem affinity purification. We describe methods for growth of worms in large-scale liquid culture, preparation of worm and embryo extracts, immunoprecipitation, and tandem affinity purification. In addition, we describe methods to test specificity of antibodies, strategies for optimizing starting material, and approaches to distinguish specific from non-specific interactions. © 2011 Elsevier Inc.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Affinity; Culture; Epitope; Immunoblotting; Immunoprecipitation; Polyclonal